ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS 3 SDN MANGLI 02 JEMBER - Krismawati, Agustin; Arigethi, Vinda Putri; Prayogo, Muhammad Suwignyo (Universitas Tanjungpura, 2024)
The success of the teaching and learning process is determined by the teaching model, namely the way the teacher conveys the material to be taught. In its truest sense, method means